The mathematic model of the building and analyze make use of the converter voltage (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2009)
This article presents methodize and analyze of the results for the connection source energy with execution devices through the operation transmitter.